USE OF PLAY AS A SOURCE OF PLEASURE AND LEARNING (Fiep Bulletin - online, 2014)
Currently the Physical Education has been the scene of numerous discussions and reflections by academic and professional community in this area, particularly on the pedagogical practice of teachers in school. Therefore this study aimed to identify which Pedagogical Approach Physical Education are known and used by teachers for teaching this subject at school. The sample consisted of thirty-two physical education teachers who work in public schools located in Campina Grande, PB. We used to collect information a questionnaire with objective and subjective. The data were interpreted by content analysis. The results show that 28 (twenty eight) teachers claim to know the Pedagogical Approaches of Physical Education and 06 (six) know them. We identified that among the Physical Education Pedagogical approaches that teachers use in their daily practice, the most cited were: Constructivist, surpassing the Critic, PCNs, Psychomotricity, Developmental, Physical Education Plural, Open Classes, Critical emancipatory, Health, Humanist, Games Cooperative. Some issues were raised with this study, the first is that it is necessary that a study to compare the knowledge about the approaches used by teachers with the practical reality of classes in school. The second issue that is pointed on the definition of one or more approaches to support the practice of the teacher in the school. A third issue is related to our study which showed that teachers know the approaches, but in the study group 18% do not know and therefore do not use the approaches in their practices.
Keywords: Physical Education; Pedagogical Approaches; Knowledge; Pedagogical Practice.